4(х²-х)²+9(х²-х)+2=0
Замена х²-х = t
4t²+9t+2=0
4t²+8t+t+2=0
4t(t+2)+1(t+2)=0
(t+2)(4t+1)=0
t=-2 или t=-0,25
Возвращаюсь к замене:
1) х²-х=-2
х²-х+2=0
D=1²-4*1*2=-7 < 0, корней нет
2) х²-х=-0,25
Домножим на 4:
4х²-4х+1=0
(2х-1)²=0
х=0,5
Единственный корень х=0,5
4(х²-х)²+9(х²-х)+2=0
Замена х²-х = t
4t²+9t+2=0
4t²+8t+t+2=0
4t(t+2)+1(t+2)=0
(t+2)(4t+1)=0
t=-2 или t=-0,25
Возвращаюсь к замене:
1) х²-х=-2
х²-х+2=0
D=1²-4*1*2=-7 < 0, корней нет
2) х²-х=-0,25
Домножим на 4:
4х²-4х+1=0
(2х-1)²=0
х=0,5
Единственный корень х=0,5